Analysis and simulation of the atmospheric and hydrological processes using the WRF atmospheric model in Peru during 2011 - Rojas, Noelia (2020)
The objective of this work has been to analyze and simulate the interactions of atmospheric and hydrological processes using the WRF Model (Weather Research and Forecasting) in Peru for the year 2014. SENAMHI records precipitation data through a meteorological network found distributed in almost all the Peruvian territory. Due to precipitation has a high spatial variability and to the scarcity of rain gauges, the use of TRMM images was used to estimate precipitation and the WRF atmospheric model to analyze the interactions of atmospheric and hydrological processes during different periods and considering the cumulus parameterizations (Kain-Fritsch scheme, KF) and microphysics (Thompson scheme). Thirty- six images of accumulated monthly precipitation over Peru were processed using the simulation of the atmospheric model WRF (two cases) and the TRMM. Twelve meteorological stations distributed by Peru were considered for the temporal analysis of the annual accumulated precipitation for 2014. The accumulated precipitation data in-situ, satellite and simulated by the WRF model were compared. An overestimation of the precipitation data was observed using the WRF model with respect to the in-situ data and a super-estimate using the TRMM satellite for all the year 2014. Using the statistical analysis and detection rates, it was concluded that during the Summer (December-March) the WRF model is more sensitive (high overestimation) for all meteorological stations located at a lower altitude in Peru. During the months of June - August there is a shortage of precipitation over Peru. The TRMM was shown to be less efficient than the WRF model. Finally, in this work it was shown that the KF scheme has a greater capacity to simulate precipitation data compared to the Thompson scheme, with two schemes not suitable for the study area being the same